Limiting physical properties of Technosols formed by the Fundão dam failure, Minas Gerais, Brazil - Betsy Carolina Muñoz de Páez; Moacir de Souza Dias Junior; Eduardo da Costa Severiano; Marco Aurélio Carbone Carneiro; Paula Cristina Caruana Martins (Revista Brasileira de Ciência do Solo, 2024)
ABSTRACT Physical properties of the Technosols formed by the tailings deposition may constitute a physical barrier that limits water movement and plant development due to the properties received from those sediments. This study aimed to evaluate the physical quality of the Technosols formed by the deposition of sediments displaced by the Fundão Dam failure, Mariana, Minas Gerais State, Brazil, based on the evaluation of physical properties and Load Bearing Capacity Models (LBCM). For that, three areas under different vegetation types were selected: eucalyptus (Euc), forest with human-assisted revegetation (RF), and forest with native vegetation (NF). Three sampling subareas were demarcated in each area: non-impacted areas (Ni), and Technosols formed in directly impacted areas (Di), and partially impacted areas (Pi). Undisturbed samples were collected in two layers and subjected to the uniaxial compression test after equilibration at five matric potentials. Soil compression curves and LBCM were determined. Soil bulk density (BD), total porosity (TP), organic matter (OM), granulometry, and particle density (PD) were also determined. Clay content was less significant, and the silt and very fine sand content was significantly higher in the Technosols, generating an increase in BD and reduction in TP. Technosols generally exhibited greater load-bearing capacity due to higher pre-consolidation pressure values attained by these soils due to the lower clay and OM contents. High resistance of these soils is one limitation for revegetation of the areas evaluated, being necessary management practices to improve physical properties of the Technosols.